Bond behaviour between recycled aggregate concrete and glass fibre reinforced polymer bars. (1st March 2016) - Baena, M.; Torres, L.; Turon, A.; Llorens, M.; Barris, C.
Highlights: Relation between use of RCA and variation in fc does not respond to a common pattern. Using RCA causes no significance change in bond development and deterioration process. Substituting NA with a RCA causes no significant change in the bond-slip curves. Greater bond strengths are obtained in the RAC for the increasing concrete grades. Bond strength predictions using CEB-FIP model code compare well with experimental results. Abstract: The use of recycled aggregate concrete (RAC) contributes to reducing energy and natural resource consumption in the construction industry. However, incorporating recycled concrete aggregates (RCA) into the concrete production process usually causes some difficulties in controlling fresh and hardened concrete properties. One of the properties susceptible to being affected is bond, which is a requirement for reinforced concrete (RC) structures. Besides, if more sustainable and durable structures are to be had, the benefits of fibre reinforced polymer (FRP) bars should be included to achieve this. This study evaluates the effect on the bond behaviour between concrete and FRP bars when a percentage of natural coarse aggregates is replaced by recycled concrete coarse aggregates. To that end, a total of 48 pull-out tests were conducted. Three series of concrete mixes (i.e. three different concrete grades) were prepared, each containing four mixes, where the RCA were used at rates of 0%, 20%, 50% and 100% of the coarse aggregate total weight. The study also focuses on the influence of the rebar surface configuration (spirally wounded and ribbed) on FRP–RAC bond strength. According to the experimental results, no unique pattern for concrete compressive strength variation after RCA has been included can be defined as being valid for all concrete grades. Furthermore, the experimental results showed that both bond development and the deterioration process between the RAC and FRP bars was similar to that between natural aggregate concrete (NAC) and FRP bars.